2014
DOI: 10.3892/mmr.2014.2686
|View full text |Cite
|
Sign up to set email alerts
|

Increased peroxisome proliferator-activated receptor γ expression levels in visceral adipose tissue, and serum CCL2 and interleukin-6 levels during visceral adipose tissue accumulation

Abstract: Abstract. This study was conducted to determine the mRNA and protein expression levels of peroxisome proliferator-activated receptors (PPARs) in visceral adipose tissue, as well as serum adipokine levels, in Sprague Dawley rats. The rats were fed either a normal (control rats) or excessive (experimental rats) intake of food for 8 or 16 weeks, then sacrificed, at which time visceral and subcutaneous adipose tissues, as well as blood samples, were collected. The mRNA and protein expression levels of PPARs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…The present study identified BRS3 and UCP1 as DEGs in visceral adipose tissue of rats with an excess dietary intake. The gene network may be associated with PParG, as increased expression of PParG was detected in visceral adipose tissue in our previous study (18). PParG, which is widely described as playing an important role in adipocyte proliferation and differentiation, as well as in the conversion of various cells into adipose-like cells (25)(26)(27)(28)(29)(30), was implicated in the visceral adipose tissue accumulation of the experimental rats in the present study.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…The present study identified BRS3 and UCP1 as DEGs in visceral adipose tissue of rats with an excess dietary intake. The gene network may be associated with PParG, as increased expression of PParG was detected in visceral adipose tissue in our previous study (18). PParG, which is widely described as playing an important role in adipocyte proliferation and differentiation, as well as in the conversion of various cells into adipose-like cells (25)(26)(27)(28)(29)(30), was implicated in the visceral adipose tissue accumulation of the experimental rats in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…PParG, which is widely described as playing an important role in adipocyte proliferation and differentiation, as well as in the conversion of various cells into adipose-like cells (25)(26)(27)(28)(29)(30), was implicated in the visceral adipose tissue accumulation of the experimental rats in the present study. PParG expression is also potentially associated with serum levels of c-c motif chemokine ligand 2 and interleukin-6 in rats (18), which may facilitate the accumulation of visceral adipose tissue, indicating that PParG serves a role in this phenomenon. However, whether PParG is directly or inversely associated with BrS3 and ucP1 in visceral adipose tissue accumulation needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations